Vivências e experiências de professores homens na educação infantil: entre práticas e sentidos - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The school is a key place for building social life. Therefore, several situations that provoke problematization and reflection appear from there... Based on that, this research intends to unveil the experiences of male teachers in the childhood education classroom in the city of Goiânia / GO, so that, to achieve this, it is necessary to unfold in specific goals, namely: it is necessary to split it into specific goals, namely: (I) to understand the historical trajectory of education in which the construction of teaching knowledge is consolidated and its reflections in the experiences and experiences of teachers; (ii) to comprehend the meanings that enable the performance of teachers to exercise the teaching practices in early childhood education; and, (iii) to understand the sociocultural perception of teachers in their teaching practices in early childhood education. The theoretical framework is based on the works of Chamon and Sales (2011); Tardif (2000, 2008, 2014) to discuss the formation of teacher identity; Nóvoa (1995, 2022); Cambi (1999); Louro (2014); Pereira (2016); Freire (2019, 2020, 2021); Ariès (1986) to reflect on early childhood education from a critical view. The results show the period of sensitive listening and dealing with the narrative of male teachers in early childhood education to understand what has emerged from these stories and how the treatment of these events can encourage (or not) the presence of more men in these environments. It is also possible to provide an opportunity to uncover phenomena that lead to a need for intervention in teacher training, with the identification-whenever is possible – of the convention that a man's body, by a shallow corporeal analysis, cannot be foreign to a process of early childhood education, being always provoked to criticize the system and fight the limitations found in education. Thus, it was noticed that even with all the issues related to the challenges of the performance of man in Early Childhood Education, the teaching practice finds gaps to (trans)form and (re) signify his practice. Since the teacher working in this educational phase is allowed to enjoy the joys found in living with children.
Experiences of male teachers in the childhood education: between practices and meanings
Keywords: Práticas docentes - Homens - Educação na infância; Docentes homens - educação na infância; Teaching practices - Mans - early childhood education; Male teachers - Early childhood education; CIENCIAS HUMANAS::EDUCACAO; FUNDAMENTOS DA EDUCACAO::SOCIOLOGIA DA EDUCACAO